2003
DOI: 10.1002/eji.200324324
|View full text |Cite
|
Sign up to set email alerts
|

A phenotypically distinct subset of immature B cells exhibits partial activation, increased survival, and preferential expression of VhS107

Abstract: We have observed that immature B cells (IgM low IgD -) in the bone marrow of adult BALB/c mice exhibit heterogeneity, with a distinct subpopulation (˚4-10%) expressing the CD43/S7 surface protein. These CD43/S7 + immature B cells often express other surface antigens associated with B cell activation (CD5, CD11b, PD-1). Generation of optimal numbers of CD43/S7 + immature B cells requires expression of a functional Btk protein, consistent with activation as a requisite for the CD43/S7 + immature B cell phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 49 publications
3
14
0
Order By: Relevance
“…30 Consistent with this result, we found that whereas frequencies of CD23 Ϫ AA4 ϩ BM B cells were unaffected in C57BL/6 mice congenic for the xid mutation (termed B6.xid), frequencies of CD23 ϩ AA4 ϩ BM B cells were reduced 2-to 3-fold in homozygous B6.xid females ( Figure 4A). Similarly, analysis of A/WySnJ mice, characterized by a null mutation in the locus encoding the antiapoptotic BLyS receptor BR-3, showed that frequencies and absolute numbers of both AA4 ϩ sIgM high CD23 ϩ BM cells and splenic T2 (and T3) B cells declined at least 2-fold compared to age-matched control A/J mice ( Figure 4B; Table 1).…”
Section: Survival Of Aa4 ؉ Cd23 ؉ Bm B Cells Is Btk-and Blys-dependentsupporting
confidence: 77%
“…30 Consistent with this result, we found that whereas frequencies of CD23 Ϫ AA4 ϩ BM B cells were unaffected in C57BL/6 mice congenic for the xid mutation (termed B6.xid), frequencies of CD23 ϩ AA4 ϩ BM B cells were reduced 2-to 3-fold in homozygous B6.xid females ( Figure 4A). Similarly, analysis of A/WySnJ mice, characterized by a null mutation in the locus encoding the antiapoptotic BLyS receptor BR-3, showed that frequencies and absolute numbers of both AA4 ϩ sIgM high CD23 ϩ BM cells and splenic T2 (and T3) B cells declined at least 2-fold compared to age-matched control A/J mice ( Figure 4B; Table 1).…”
Section: Survival Of Aa4 ؉ Cd23 ؉ Bm B Cells Is Btk-and Blys-dependentsupporting
confidence: 77%
“…Consistent with this hypothesis, we have previously reported that aged mice show an increased proportion of immature B cells within the bone marrow that appear to have undergone activation as evidenced by altered surface phenotype (e.g., expression of CD43, CD5, CD11b, PD-1 antigens), dependence on the BCR pathway kinase Btk, increased size, and an altered Vh repertoire as evidenced by increased usage of the VhS107 family (23,24). In this report, we show that B cells with a comparable phenotype are preferentially derived from preBCR deficient c-kit + pre-B cells within the B2 lineage.…”
Section: Introductionsupporting
confidence: 69%
“…We have previously reported that, in vivo, aged mice often have an increased frequency of immature bone marrow B cells characterized by higher surface expression of CD43 (recognized by the S7 monoclonal antibody) and increased cell size (23,24). In order to determine if this phenotype was associated with the origin of the B cell precursors (e.g., c-kit - vs. c-kit + ), and noting the increased proportion of c-kit + vs. c-kit - pre-B cells in aged mice, we compared immature B cells derived from c-kit + wild-type and λ5 knockout precursor cells with those derived from c-kit - B cell precursors in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Existence of independent B lineages that specifically express the V1 gene and require Bright might explain our observations. A small subpopulation (4–10%) of immature bone marrow B cells was identified which preferentially expressed the S107 gene in Balb/c mice (54). However, it is not clear that these cells represent an independent lineage of B cells.…”
Section: Discussionmentioning
confidence: 99%